Meniscus Body Position, Size, and Shape in Persons With and Persons Without Radiographic Knee Osteoarthritis: Quantitative Analyses of Knee Magnetic Resonance Images From the Osteoarthritis Initiative. Issue 7 (2nd July 2013) - Wenger, Andrea; Wirth, Wolfgang; Hudelmaier, Martin; Noebauer‐Huhmann, Iris; Trattnig, Siegfried; Bloecker, Katja; Frobell, Richard B.; Kwoh, C. Kent; Eckstein, Felix; Englund, Martin
Abstract : Objective: To quantitatively evaluate the position, size, and shape of the menisci in subjects with radiographic knee osteoarthritis (OA) compared to subjects without OA, using magnetic resonance imaging (MRI). Methods: We studied the right knees of 39 Osteoarthritis Initiative participants (24 women and 15 men with a mean age of 59.6 ± 8.7 years) with medial compartment radiographic tibiofemoral OA (Kellgren/Lawrence grade of 2 or 3). Subjects were matched individually for age, sex, and height to controls without knee OA and without risk factors for knee OA. The right knees of the controls were used as references. One observer performed manual segmentation of the tibial plateau and the medial and lateral meniscus based on a coronally reconstructed double‐echo steady‐state sequence with water excitation, focusing on 5 central 3T MRIs. Results: In OA knees, there was less meniscal coverage of the medial tibial plateau (435 mm 2 versus 515 mm 2 ; P = 0.0004), the medial meniscus body showed more extrusion (2.64 mm versus 0.53 mm; P < 0.0001), and the peripheral margin had a more convex shape, i.e., bulged more (mean 0.61 mm versus 0.27 mm; P < 0.0001). The thickness or volume of the medial meniscus body of OA knees did not differ substantially from reference knees. In contrast, in OA knees the lateral meniscus body had a larger volume (mean 266 mm 3 versus 224 mm 3 ; P = 0.0005) and extruded more (mean 1.16 mm versus −1.01 mm; P < 0.0001), and the external margin bulged more (mean 0.53 mm versus 0.35 mm; P < 0.0001), than in reference knees. Conclusion: Our findings indicate altered meniscal position and shape (i.e., more bulging) in both compartments in medial compartment knee OA. These changes may be important features of OA pathogenesis and/or disease consequences.